A proposed proposal for curricula of Islamic education system of decisions of general programs in the light of human rights - Al- Omari, Mohammed Ali; Ali, Amal Mahmoud (Journal of Educational and Psychological Sciences, 2019)
This study aims to formulate a new vision. The curricula of Islamic education in the secondary stage have general programs in the light of human rights, so that the authors of Islamic education curricula in the Kingdom of Saudi Arabia will develop these curricula in the light of the human rights set forth in this study. And strengthen the strengths and propose remedial measures for the weaknesses and shortcomings in the curricula of Islamic education in the light of human rights. It also aims to include human rights in Islam in the content of the curricula of the Islamic education curriculum for the secondary stage system of general programs courses. Through the analysis of the content, the proposed vision here is what the researcher hopes to find solutions to include those rights. And seeks to provide procedural recommendations to overcome the obstacles that prevent the inclusion of these concepts and values ​​in line with the data in contemporary times, as well as propose the mechanisms necessary to implement this vision.